2019 Annual Report Research, Industrial Linkages and Alumni Division UiTM Cawangan Johor - Mohamad Shafi, Dr Roslina; Ismail, Dr Noriah; Arbin, Dr Norazam; Haris, Sharazad; Sa'udah @ Suhadak, Nurulzulaiha; Zainuddin, Noor Azrin; Isahak, Siti Nordiyana; Abu Bakar, Ir.Ts Azinoor Azida; Wee, Lee Siong; Markom, Dr. Arni Munira; Abdullah, Mohammad; Sidik, Norbaiti; et al. (Research, Industrial Linkages and Alumni Division, 2019)
The Intellectual Prestige (i-PRESTIGE) 2019 marks the second compilation and publication of reports from the different units under the Research, Industrial Linkages and Alumni Division of UiTM Cawangan Johor. Like the maiden publication, it highlights the success and achievements of PJI&A of UiTMCJ in relation to research, publications, consultancy projects, innovations, entrepreneurship, community services and alumni activities.